Optimalisasi Badan Amil Zakat Nasional Dalam Upaya Penyaluran Dana Zakat Melalui Program Sleman Cerdas Terhadap Peningkatan Pendidikan - Iqbal, Ahmad; Yusdani, Yusdani; Ramdani Harahap, Soritua Ahmad (Jurnal Ilmiah Ekonomi Islam, 2024)
Education is one of the Indonesian nation's development sectors to advance society in forming intellectual human resources. It is very important to pay attention to contributions in the field of education, one of which is the use of zakat funds as a solution for children who are less fortunate in terms of education. Even so, it turns out that there are still many people who have not been touched by educational assistance through zakat. This research was conducted in 4 different places, namely at the BAZNAS Sleman Office, SD Negeri Perumnas 3, MTs N 4, and MAN 5 Sleman. The research method used is a qualitative method with a normative juridical and sociological approach. The results of this research are the distribution of zakat funds at BAZNAS Sleman with 5 work programs. The 5 work programs consist of: Productive Sleman, Healthy Sleman, Smart Sleman, Careful Sleman and Taqwa Sleman. Apart from that, BAZNAS Sleman also coordinates with Islamic organizations such as Nahdatul Ulama and Muhammadiyah so that there is no overlap with each other. In particular, the Sleman Pintar program is implemented in coordination with the Education Department and also the Social Service so that it is right on target and helps education to create a superior generation in the future.